2010
DOI: 10.1007/s10741-010-9166-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in heart failure associated with aging

Abstract: Heart failure is a progressive disease, leading to reduced quality of life and premature death. Adverse ventricular remodeling involves changes in the balance between cardiomyocyte protein synthesis and degradation, forcing these myocytes in equilibrium between life and death. In this context, autophagy has been recognized to play a role in the pathophysiology of heart failure. At basal levels, autophagy performs housekeeping functions, maintaining cardiomyocyte function and ventricular mass. Autophagy also oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
87
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 52 publications
1
87
0
1
Order By: Relevance
“…However, perhexiline has also been shown to inhibit the mammalian target of rapamycin complex 1 (mTORC1; Balgi, et al, 2009), an effect which is shared by amiodarone. The mTOR-signaling pathway relays signals of adequate energy supplies to inhibit cardiomyocyte autophagy, which is over-activated (due to AMPK activation, which inhibits mTOR; Matsui, et al, 2007) and maladaptive in the hypertrophic failing heart (De Meyer, et al, 2010). This ancillary property of perhexiline is likely to affect the careful balance of cardiac autophagy and therefore disease progression and prognosis in HF, however further investigation is needed to test this.…”
Section: Carnitine Palmitoyltransferase 1 (Cpt1) Inhibitionmentioning
confidence: 99%
“…However, perhexiline has also been shown to inhibit the mammalian target of rapamycin complex 1 (mTORC1; Balgi, et al, 2009), an effect which is shared by amiodarone. The mTOR-signaling pathway relays signals of adequate energy supplies to inhibit cardiomyocyte autophagy, which is over-activated (due to AMPK activation, which inhibits mTOR; Matsui, et al, 2007) and maladaptive in the hypertrophic failing heart (De Meyer, et al, 2010). This ancillary property of perhexiline is likely to affect the careful balance of cardiac autophagy and therefore disease progression and prognosis in HF, however further investigation is needed to test this.…”
Section: Carnitine Palmitoyltransferase 1 (Cpt1) Inhibitionmentioning
confidence: 99%
“…The basal autophagy in the heart antagonizes ventricular hypertrophy by increasing protein degradation, which decreases the tissue mass. 265 The rate of protective autophagy in the heart declines with age, which is associated with an age-dependent decline in cardiac function. 265 Muscle weakness is also a harmful symptom in elderly individuals.…”
Section: Autophagy In Kidney Agingmentioning
confidence: 99%
“…265 The rate of protective autophagy in the heart declines with age, which is associated with an age-dependent decline in cardiac function. 265 Muscle weakness is also a harmful symptom in elderly individuals. Mice lacking macroautophagy activity by deletion of the Atg7 gene in skeletal muscle show accumulation of abnormal mitochondria, which causes age-dependent muscle atrophy and a decrease in force.…”
Section: Autophagy In Kidney Agingmentioning
confidence: 99%
“…Preclinical studies have demonstrated that autophagy is associated with cancer, neurodegenerative disorders (eg, Alzheimer, Parkinson, and Huntington diseases), embryogenesis, aging, and immunity, and also with cardiovascular disease, including ischemia-reperfusion injury of the heart, cardiomyopathy, and atherosclerosis. [5][6][7][8][9] Despite tremendous recent advances in the field, the functional significance of autophagy in human disease remains incompletely understood and potentially involves both adaptive and maladaptive outcomes. Nonetheless, a growing body of evidence suggests that manipulation of the signaling pathways regulating autophagy provides novel therapeutic strategies in the prevention or treatment of human disease, as discussed for atherosclerosis in more detail below.…”
mentioning
confidence: 99%